1971
DOI: 10.1037/h0031111
|View full text |Cite
|
Sign up to set email alerts
|

Reappraisal of the A-B therapist "type" distinction in terms of the Personality Research Form.

Abstract: The A-B therapist "type" distinction, usually made on the basis of a small set of interest items, has proven predictive of therapist-patient compatibility in several clinical and analogue studies. To assess the personality dimensions involved in the A-B distinction among undergraduate males (# = 223), their A-B scale scores were related to the 22 variables of Jackson's Personality Research Form. Multiple discriminant analyses and factor analyses strongly supported the hypothesis that A-B status is explicable i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
14
1

Year Published

1975
1975
1981
1981

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 22 publications
3
14
1
Order By: Relevance
“…As, on the other hand, talked about themselves (self-tag), were less defensive (in the social desirability sense), and had more feminine interests. These differences concur rather well with descriptions of A and B males as noted by Johnson et al (1973), Berzins et al (1971), andDublin et al (1969).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As, on the other hand, talked about themselves (self-tag), were less defensive (in the social desirability sense), and had more feminine interests. These differences concur rather well with descriptions of A and B males as noted by Johnson et al (1973), Berzins et al (1971), andDublin et al (1969).…”
Section: Discussionsupporting
confidence: 91%
“…Their findings suggest that As were more introspective and less defensive (in a socially desirable sense) than Bs. Berzins, Barnes, Cohen, and Ross (1971) also found Bs to be more concerned with presenting themselves in a positive light, using the Jackson Personality Research Form. Dublin, Elton, and Berzins (1969), using the Omnibus Personality Inventory, found the dimension of masculinity-femininity to be the best linear predictor of A-B status.…”
mentioning
confidence: 93%
“…Finally, it is apparent that apart from loworder correlations suggesting a positive relation of Masculinity scores to beliefs in internal control, significant among men and for the BSRI among women, little variance is shared between these sex role measures and beliefs in internal-external control. As noted elsewhere (Berzins, Note 6), the best predictor of locus of control is the FRF Desirability scale, probably because it contains an appreciable self-esteem component (see Table 2) and has in fact been construed as a measure of self-esteem in a prior study (Berzins, Barnes, Cohen, & Ross, 1971).…”
Section: Convergent and Discriminant Validitymentioning
confidence: 66%
“…Several explanatory formulations of the A-B interaction effects (e.g., the "complementarity" hypothesis, perceptual-cognitive style compatibility) have been proposed. One such formulation can be called the personological hypothesis, which evolved from a study by Berzins, Barnes, Cohen, and Ross (1971), who showed that A-B differences can be explained in personality terms. Using the Personality Research Form (PRF, Jackson, 1967), they found that A-type persons were characterized by cautious self-expression, social ineptness, and a restricted cognitive scope, whereas B subjects appeared socially ascendant and "open" to complex experiences.…”
mentioning
confidence: 99%
“…The single most differentiating personality dimension was "harmavoidance" (As>Bs), denoting cautious avoidance of risk taking. Berzins, Dove, and Ross (1972) cross-validated the Berzins et al (1971) study with very large samples of college males and females, male therapists, and male college clinic patients. In spite of striking intergroup differences in PRF scale scores, A and B persons, across samples, showed distinctive personality profiles.…”
mentioning
confidence: 99%